2005
DOI: 10.1016/j.chemosphere.2005.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between cadmium and atrazine during uptake by rice seedlings (Oryza sativa L.)

Abstract: The uptake of atrazine by rice seedlings (Oryza sativa L.) through plant roots from nutrient solution was investigated in the presence and absence of Cd 2+ over an exposure period of four weeks. It was found that both atrazine and Cd 2+ were toxic to rice seedlings. Both shoot and root biomasses decreased when the seedlings were exposed to increasing atrazine or Cd 2+ concentrations in nutrient solutions. In the absence of Cd 2+ , a linear relationship was observed between atrazine concentrations in roots/shoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
22
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 24 publications
(34 reference statements)
7
22
0
Order By: Relevance
“…1.). In agreement with our results Su et al (2005) found that when atrazine and Cd 2+ concentrations in solution were maintained at mole ratios of 1:1, 1:2 or 2:1, the interaction between atrazine and Cd 2+ was different. More experimentation should be considered to better understand the mechanisms underlying the different ratio of butachlor and Cd concentration in soils.…”
Section: Combined Effects Of CD and Butachlor On Soil Enzyme Activitiessupporting
confidence: 94%
See 1 more Smart Citation
“…1.). In agreement with our results Su et al (2005) found that when atrazine and Cd 2+ concentrations in solution were maintained at mole ratios of 1:1, 1:2 or 2:1, the interaction between atrazine and Cd 2+ was different. More experimentation should be considered to better understand the mechanisms underlying the different ratio of butachlor and Cd concentration in soils.…”
Section: Combined Effects Of CD and Butachlor On Soil Enzyme Activitiessupporting
confidence: 94%
“…The effect of combined pollution depends on the constituents of the mixture and may vary significantly (Jensen & Sverdrup, 2002). In many cases, HM and herbicides are frequently found together as contaminants in soils (Su, Zhu, Lin, & Zhang, 2005). Although numerous papers have dealt with the toxicity and fate of Cd and butachlor (Landi, Renella, Moreno, Falchini, & Nannipieri, 2000;Min et al 2002;Sapna, Natarajan, & Govindaswamy, 1995), few studies have focused on their effects as mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…However, the wide-use and persistent residues of herbicides in soils have brought about great concerns on toxic impacts on plant growth, development and crop productivity (Su et al, 2005;Sathiakumar et al, 2011;Lu et al, 2013). Fortunately, plants have evolved sophisticated strategies to cope with the adverse effects of herbicide by attenuating the phytotoxicity (Kawahigashi, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Atrazine (2-chloro-4-ethyamino-6-isopropylamino-s-triazine, ATR) belongs to the triazine herbicide family that controls many broadleaf and grassy weeds in areas of graminaceous crop production such as corns and sorghums (Su et al, 2005). The action mode of atrazine is the selective repression of photosynthesis II by blocking the electron transport to generate reactive oxygen species (Anderson and Zhu, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Contamination of plants, especially the food crops, which serve as the first link of the food-chain process, influences human health closely as they are more susceptible to contamination by pollutants in soil (Mclachlan, 1996;Su et al, 2005a;Su et al, 2005b;Zhu, 2005, 2006). Thus, HCB contamination of crops deserves attention.…”
Section: Introductionmentioning
confidence: 99%